IrMn as exchange-biasing material in systems with perpendicular magnetic anisotropy - VAN DIJKEN, SEBASTIAN; COEY, JOHN MICHAEL DAVID (American Institute of Physics, 2005)
Contact between a Co/Pt multilayer and an IrMn film leads to perpendicular exchange bias. The exchange bias field does not depend on the degree of (111) film texture and for Co/Pt multilayers with IrMn at the bottom it can be enhanced by magnetic field annealing. The perpendicular exchange bias of the Co/Pt?IrMn system is limited by a misalignment between the Co spins and the film normal, which is due to a negative magnetic anisotropy contribution from the Co/IrMn interface (KSCo/IrMn = ?0.09?mJ/m2). The insertion of a 3?? thick Pt layer at the Co/IrMn interface maximizes the perpendicular exchange-bias field.
PUBLISHED
Keywords: Physics